2009
DOI: 10.1021/es9010338
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Iodinated Organic Compounds by Oxidation of Iodide-Containing Waters with Manganese Dioxide

Abstract: This study shows that iodinated organic compounds can be produced when iodide-containing waters are in contact with manganese oxide birnessite (delta-MnO2) in the pH range of 5-7. In the absence of natural organic matter (NOM), iodide is oxidized to iodate that is also adsorbed onto delta-MnO2. In the presence of iodide and NOM, adsordable organic iodine compounds (AOI) are formed at pH < 7 because of the oxidation of iodide to iodine by delta-MnO2 and the reactions of iodine with NOM. In addition, iodoacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
95
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 37 publications
2
95
1
Order By: Relevance
“…Furthermore, their study indicated that iopamidol can form the most appreciable level of I-DBPs compared to iohexol and iopromide, another two species of ICM [10]. Some researchers have studied the formation of I-DBPs using different disinfectants including chlorine, chloramine, ozone, potassium permanganate, chlorine dioxide and manganese dioxide [13] and [14]. Bichsel and von Gunten [13] proved that chloramine can form significant amount of I-DBPs because it cannot oxidize the reactive hypoiodous acid (HOI) to the stable iodate so that the reaction between HOI and natural organic matter (NOM) leads to the formation of I-DBPs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their study indicated that iopamidol can form the most appreciable level of I-DBPs compared to iohexol and iopromide, another two species of ICM [10]. Some researchers have studied the formation of I-DBPs using different disinfectants including chlorine, chloramine, ozone, potassium permanganate, chlorine dioxide and manganese dioxide [13] and [14]. Bichsel and von Gunten [13] proved that chloramine can form significant amount of I-DBPs because it cannot oxidize the reactive hypoiodous acid (HOI) to the stable iodate so that the reaction between HOI and natural organic matter (NOM) leads to the formation of I-DBPs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous terrestrial organisms are able to synthesise organohalogen compounds, many of which belong to the fungi family (Gribble, 2003). In general it is thought that iodination of organic macromolecules is enzymatically driven (haloperoxidase), although there is also evidence for abiotic mechanisms Gallard et al, 2009). To date, organically bound iodine in freshwaters has predominantly been observed in humic rich environments such as peat bogs (Biester et al, 2006) and waste waters (Rädlinger and Heumann, 2000), where organic carbon concentrations can exceed 50 mg l À1 and organically bound iodine concentrations range from 10 to 20 lg l À1 .…”
Section: Introductionmentioning
confidence: 99%
“…It would be premature to conclude whether abiotic processes, e.g. oxidation on Birnessite (Gallard et al, 2009), or biotic processes, e.g. oxidation in parallel with nitrification (Truesdale et al, 2001), are principally responsible for iodide oxidation to iodate in saline groundwater, because the field evidence supports both pathways (Fox et al, 2010;Ž ic et al, 2010).…”
Section: Inorganic Iodine Redox Transformationsmentioning
confidence: 99%
“…oxidation in parallel with nitrification (Truesdale et al, 2001), are principally responsible for iodide oxidation to iodate in saline groundwater, because the field evidence supports both pathways (Fox et al, 2010;Ž ic et al, 2010). Nevertheless, oxidation by birnessite would promote formation of organic iodine in these environments (Gallard et al, 2009) because of the higher dissolved organic carbon concentrations (Cuculić et al, 2010). As a result, we suggest that a process which includes nitrifying bacteria and/or archaea is the more likely, particularly as biotic mechanisms are preferred in ocean waters and at the sediment-water interface (Anschutz et al, 2000).…”
Section: Inorganic Iodine Redox Transformationsmentioning
confidence: 99%